THE INFLUENCE OF JOB EMBEDDEDNEES ON TURNOVER INTENTIONS AMONG ADVERTISING MANAGERS - DeConinck, Jim; Johnson-Busbin, Julie; DeConinck, Mary Beth; Busbin, James (Archives of Business Research, 2019)
In recent years, job embeddedness has been the focus of extensive research because of its relationship to employees’ turnover behavior. This research developed and tested a model, with a sample of advertising managers, examining the role of perceived supervisor support (PSS) as a mediator between organizational justice and job embeddedness. Distributive justice, interactional justice, and procedural justice were predictors of PSS. The relationship between organizational justice and job embeddedness was indirect through PSS. The results have important implications for controlling turnover.